2015
DOI: 10.1016/j.bbrc.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-induced glutathione reduction in mitochondria is involved in the first phase of pancreatic β-cell insulin secretion

Abstract: Glucose-induced glutathione reduction in mitochondria is involved in the first phase of pancreatic β-cell insulin secretion, ABSTRACT Glucose can acutely reduce mitochondrial glutathione redox state in rat islets.However, whether glucose-stimulated mitochondrial glutathione redox state relates to glucose-stimulated insulin secretion (GSIS) remains unknown. We used genetically encoded redox-sensitive GFPs to target the mitochondria to monitor glutathione redox changes during GSIS in rat pancreatic β-cells. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…31 Moreover, PDI did not facilitate oxidative folding of proinsulin in the ER of pancreatic β cells and had been implicated in retrotranslocation of certain ER-associated degradation (ERAD) substrates. 34 Substantial evidence suggested glutathione was a fundamental function in cellular redox homeostasis, 35,36 and cytosol derived reduced glutathione (GSH) could enter endoplasmic reticulum (ER), which did not only as an indicator of oxidative stress but also played an essential role on the rearrangement of aberrant disulfide bonds. 37 Additionally, reactive oxygen species (ROS) plays an essential role in GSIS, and induction of endogenous antioxidative enzymes in β cells abrogates ROS signaling and reduces GSIS.…”
Section: Discussionmentioning
confidence: 99%
“…31 Moreover, PDI did not facilitate oxidative folding of proinsulin in the ER of pancreatic β cells and had been implicated in retrotranslocation of certain ER-associated degradation (ERAD) substrates. 34 Substantial evidence suggested glutathione was a fundamental function in cellular redox homeostasis, 35,36 and cytosol derived reduced glutathione (GSH) could enter endoplasmic reticulum (ER), which did not only as an indicator of oxidative stress but also played an essential role on the rearrangement of aberrant disulfide bonds. 37 Additionally, reactive oxygen species (ROS) plays an essential role in GSIS, and induction of endogenous antioxidative enzymes in β cells abrogates ROS signaling and reduces GSIS.…”
Section: Discussionmentioning
confidence: 99%
“…While more-reduced redox centers drive hyperpolarization of ΔψM in general, fluxes through mitochondrial metabolism and the respiratory chain are also greatly increased during GSIS, making predictions of the redox states of actual ROS-forming centers difficult. ROS levels in turn are also defined by their removal, which is known to increase when glucose is present [91].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that the Grx system has positive impact on insulin secretion [16, 46, 47]. Furthermore, tissue-specific expression of Grx was reported [48].…”
Section: Discussionmentioning
confidence: 99%